No fair! - Grant, Jacob, 1984- (Viking, 2023)
"Pablo and his dad are ready for a fun day together at the farmer's market-what's better than a bike ride, doughnuts, and hot apple cider? But Pablo's dad says that everything Pablo picks out is too big for him. It's just no fair! What if he was in charge and his dad was the kid, Pablo wonders. And his dad stops to think about it, too. This light-hearted but thoughtful look at fairness introduces a important subject that everyone encounters throughout their lives."--